Analisis Urf Terhadap Jual Beli Borongan Sayuran Di Desa Purbosari Kecamatan Ngadirejo Kabupaten Temanggung - Sariyekti, Eko; Syaichi , Achmad; Rohiq, M. (El-Qenon: Journal of Islamic Law, 2024)
Bulk buying and selling is one of the traditions that has become customary in the community of Purbosari Village, Ngadirejo District, Temanggung Regency. From the perspective of fiqh muamalah, this practice remains a subject of study that requires solutions to address the issues related to bulk buying and selling. The aim of this research is to understand how the practice of bulk buying and selling is carried out by the community in Purbosari Village, Ngadirejo District, Temanggung Regency, and to review the practice from the perspective of urf (customary practice). This research uses a qualitative approach with a field study methodology. The data collection techniques employed include interviews, observations, and documentation with the buyers, sellers, and local officials involved in the practice. The analysis in this research involves data reduction, data presentation, and conclusion drawing. The results of the research indicate that the practice of bulk buying and selling in Purbosari Village, Ngadirejo District, Temanggung Regency is carried out by having buyers provide an advance payment to farmers, which serves as capital for their farming activities. The harvest is then sold to these buyers in bulk. This practice is an old tradition and does not have negative impacts, making it a customary practice (urf) that is still considered normal and acceptable